Successful Treatment of Stage 4 Sacral Pressure Ulcers using Vacuum-assisted Closure Therapy - Tuba Oskay* (Global Journal of Medical and Clinical Case Reports, 2025)
Abstract Pressure ulcers are a significant health issue, particularly among the elderly and immobile individuals, resulting in considerable human suffering and financial costs. They pose a clinical challenge for both healthcare providers and patients, as they can be difficult to heal, expensive to treat, with a significant negative impact on quality of life. Therefore, prevention is crucial. Here, we report the successful treatment of a 75-year-old male patient presenting with persistent sacral pressure ulcer infection with Vacuum-Assisted Closure (VAC) therapy. This patient had a history of bedridden dementia and a previous cerebral infarction, which predisposed him to persistent deep-pressure ulcers. With effective management, he experienced clinical improvement, highlighting the importance of using VAC therapy in challenging cases.